Ecoaesthetics and the Development of Ecological Thinking - Samadov Aktam Rafiqovich; Azimov Ozod Mamatkulovich Mohsin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Ecoaesthetics has emerged as a philosophical response to global ecological degradation, emphasizing that environmental awareness is strengthened when humans perceive nature through aesthetic and ethical values. Specific Background Contemporary discourse highlights that ecological thinking develops not only through scientific and political solutions but also through cultural, moral, and aesthetic engagement with the natural world, including educational reforms that embed aesthetic appreciation in ecological learning. Knowledge Gap However, limited studies integrate ecoaesthetic theory with broader ecological culture, urban planning, and pedagogical practices in a unified analytical framework. Aims This study examines the philosophical foundations of ecoaesthetics and evaluates its role in shaping ecological consciousness, cultural attitudes, and sustainable social practices. Results Findings indicate that aesthetic perception of nature enhances moral responsibility, strengthens ecological culture, and fosters pro-environmental behaviour at both individual and societal levels, with notable influence on art, education, and urban design. Novelty The study links ecoaesthetic perception with ecological ethics, cultural development, and psychological well-being, offering a multidimensional interpretation of ecological thinking. Implications Ecoaesthetics can serve as a conceptual and practical foundation for ecological education, sustainable urbanism, and cultural transformation, helping societies restore harmony between humanity and the natural environment.Highlight : Ecoaesthetics links aesthetic perception with ecological awareness, strengthening moral responsibility toward nature. Aesthetic education supports the formation of ecological culture, especially among younger generations. Integrating ecoaesthetic values into society fosters sustainable behaviour and balanced human–nature relations Keywords : Ecological Aesthetics, Ecological Thinking, Aesthetic Consciousness, Sustainable Development, Ecological Culture